2021
DOI: 10.1049/gtd2.12227
|View full text |Cite
|
Sign up to set email alerts
|

Lightning risk assessment model for transmission lines with lift‐based improved analytic hierarchy process

Abstract: This paper proposes a new assessment method for lightning trip-out of transmission lines that includes an improved analytic hierarchy process (IAHP) algorithm based on a lift in association rules. First, the k-means clustering algorithm is used to discretize the geomorphic information along transmission lines, and ten feature factors are obtained. Next, by analysing the correlation between each feature factor and a lightning trip-out event using the lift algorithm, the strong correlation factors are extracted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The method uses clustering algorithm to obtain the characteristic factors and establish an objective evaluation matrix. The empirical analysis of the model shows that the consistency between the estimated results of the model and the actual values is 76%, which is very practical [6]. Yadav proposed a decision model based on hybrid hierarchical analysis for optimal selection of dental conforming materials, and the dental composites were selected with this model, and the results showed that the model selected dental composites with better performance than other models [7].…”
Section: Literature Reviewmentioning
confidence: 89%
“…The method uses clustering algorithm to obtain the characteristic factors and establish an objective evaluation matrix. The empirical analysis of the model shows that the consistency between the estimated results of the model and the actual values is 76%, which is very practical [6]. Yadav proposed a decision model based on hybrid hierarchical analysis for optimal selection of dental conforming materials, and the dental composites were selected with this model, and the results showed that the model selected dental composites with better performance than other models [7].…”
Section: Literature Reviewmentioning
confidence: 89%
“…With GIS, users can better understand patterns, relationships, and the context of geographic information, leading to better communication and enhanced efficiency, management, and decision-making. It is also observed that there is a growing trend in the use of GIS within the electrical sector (ESRI, 2010;Husain et al, 2012;Kakumoto et al, 2016;Kezunovic et al, 2015;Korir & Ngigi, 2015;Leite et al, 2019;Li et al, 2014;Lin & Xu, 2016;Rahman et al, 2020;Yatim et al, 2019;Yan et al, 2016;Zheng et al, 2021).…”
Section: Figure 1 History Of Lightning Location System In Peninsular ...mentioning
confidence: 99%
“…Xue et al (2017) analyzed factors such as lightning properties and environmental impact on the location of conductors, and obtained the distribution pattern of lightning strikes in distribution networks, providing technical guidance for the application of overhead conductors. Zheng et al (2021) established an Analytic Hierarchy Process (AHP) structural model for lightning protection measures of transmission lines based on the AHP, and analyzed the correlation between various characteristic factors of terrain and lightning tripping. Zou et al (2016), Zhao et al (2017) quantitatively analyzed the terrain characteristics of lightning strike areas by utilizing factors such as altitude, slope, slope aspect, land use type, water area, grassland, and forest land, and drew a distribution map of lightning strike induced disaster environment.…”
Section: Introductionmentioning
confidence: 99%